Eco-warriors in the supermarket? Evaluating the UK sustainable consumption strategy as a tool for ecological citizenship - Gill Seyfang (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2004)
Ecological Citizenship is a potentially ethic-based motivation for changing behaviour towards more sustainable lifestyles. It describes citizenship as activity taken in the private as well as public sphere, and with regard to a common humanity transcending the boundaries of nation states. This paper examines ecological citizenship at perhaps its most mundane, yet its most ubiquitous and fundamental level - the choices and actions which individuals and households make on a daily basis, in the supermarket and on the high street. It deals with changing consumption patterns, consumer behaviour and lifestyles, and how these relate to environmental and social demands for sustainability. Sustainable consumption has become a core policy objective in national and international arenas, despite contested understandings of what it might mean in practice. The mainstream policy interpretation of sustainable consumption and the UK strategy is described, which relies upon individual consumers to make environmentally-motivated private decisions in order to deliver sustainability. This approach is critically evaluated on two fronts. First, a number of market failures are identified which compromise the integrity of the proposed model. Second, failures to achieve the desired impacts are revealed, which significantly limit the scope and ambition of mainstream sustainable consumption strategy. Responding to these limitations, an alternative conception of sustainable consumption is proposed, and three examples are given of practical tools and initiatives which overcome some of the obstacles faced by the mainstream approach. These are: the Measure of Domestic Progress national accounting index, localised organic food supply chains, and community currencies (time banks and LETS). The alternative strategy promotes ecological citizenship by re-creating social and economic institutions for environmental governance according to different value regimes. By combining improvements to the mainstream policy strategy, with explicit support for a diversity of alternative approaches which build new social and economic institutions for consumption, governments could harness the energies of ecological citizens to make significant strides along the road to sustainability.
Keywords: 330; ecological citizenship; environmental decision-making; government policy; institutions; Sustainable consumption and production; Umweltbewusstsein; Nachhaltige Entwicklung; Konsumentenverhalten; Großbritannien